Pengaruh Konsentrasi Gula Dan Waktu Fermentasi Terhadap Fermentasi Asam Asetat Menggunakan Kulit Nanas Dan Acetobacter Aceti - Ahmad Dedi Fadillah; Chairul Chairul; Cory Dian Alfarisi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pineapple (Ananas comosus (L) Merr) is a fruit which has a golden yellow color. Pineapple can thrive in tropical climates such as in Indonesia. Pineapple production in Indonesia in 2009 was 1,558,196 tons. The sugar contained in pineapple is 2.32% glucose, 1.42% fructose, and 7.89% sucrose. So that it can be used as an alternative material for the production of acetic acid. Acetic acid can be produced from raw materials containing starch or sugar by fermentation using microorganisms. The purpose of this study was to determine the effect of fermentation time and sugar concentration on the yield of acetic acid produced and to find out the optimal time and concentration of sugar in pineapple rind fermentation into acetic acid using Saccharomyces cerevisiae and Acetobacter aceti bacteria. The initial sugar concentration variations were 10%, 20%, and 30%, while the fermentation time was 2, 3, 4, 5, 6 days. The acetic acid fermentation process was carried out at pH 6, stirring speed 200 rpm and 10% inoculum. The test results using the Nelson-Samogyi method showed that the highest sugar concentration was 30% (174,678 g/L) of sugar added to pineapple rind raw material. The highest concentration of acetic acid was obtained 35.581 g/L and the yield of 30.555%. The best fermentation time is the 6th day of fermentation.Keywords: Acetobacter aceti, acetic acid, fermentation, inoculum, pineapple